Comparative effects of three methods of promoting breastfeeding among human immunodeficiency virus–infected women in Uganda: a parallel randomized clinical trial. Issue 6 (17th July 2018) - Namale-Matovu, Joyce; Owora, Arthur H; Onyango-Makumbi, Carol; Mubiru, Mike; Namuli, Prossy E; Motevalli-Oliner, Mahnaz; Musoke, Philippa; Nolan, Monica; Fowler, Mary G
Abstract: Background: The objective of this study was to evaluate the comparative effects of three breastfeeding promotion interventions on the duration of exclusive breastfeeding (EBF) and any breastfeeding (BF) among human immunodeficiency virus (HIV)-infected women in Uganda. Methods: Between February 2012 and February 2013, 218 HIV-infected pregnant mothers were randomly assigned to (A) standard care (n=73), (B) enhanced family/peer support (n=72) or (C) enhanced nutrition education (n=73). Results: The prevalence (%) of EBF/BF did not differ between intervention arms at the sixth (A, 85/92; B, 84/91; C, 87/89) and ninth (A, 17/91; B, 18/89; C, 16/87) postpartum month assessments (p>0.05). However, the risk of early BF cessation differed between intervention arms depending on the mother's level of formal education (p=0.04). Among women with no formal education, the risk of early BF cessation was 88% (adjusted hazard ratio [aHR] 0.12 [95% confidence interval CI 0.05–0.30]) and 93% (aHR 0.07 [95% CI 0.03–0.18]) lower in arms B and C, respectively, than in arm A (p<0.01). HIV status disclosure to a partner was associated with a higher risk of early EBF (p=0.03) and BF (p=0.04) cessation. Conclusions: In resource-limited settings, enhanced (vs standard care) EBF promotion interventions may not differentially influence EBF but reduce the risk of early BF cessation among women with no formal education. Targeted enhanced interventions among women with no formal education and a mother's partner may be critical to reducing the risk of early EBF/BF cessation.